ANALISIS GUGUS FUNGSI PADA SAMPEL UJI, BENSIN DAN SPIRITUS MENGGUNAKAN METODE SPEKTROSKOPI FTIR - Anam, Choirul; Sirojudin, Sirojudin; Firdausi, K. Sofjan (BERKALA FISIKA, 2007)
An analysis of functional groups using FTIR (Fourier Transform Infra Red) spectroscopy in test samples, such as petroleum and spiritus compound has been done.The spectral of the functional groups is observed by comparing of the absorption band which is formed on infra red spectrum with the infra red lines standard and comparing with other known compound. It is expected that functional group identification can be done effectively.Infra red spectrums of petroleum show the group of methyl (CH3), alkenes and aromatic compound. That results analysis is supported by appearance of bending symmetric vibration of C-H and the presence of stretching vibration of C=C from aromatic ring. The spiritus spectrums show the group of hydroxyl from alcohol compound. That analysis is supported by appearance of wide band on 3500–3000 cm-1 and appearance of band on 1000–1100 cm-1. While test sample spectrum show the group of hidroksil (O-H) from primary alcohol, group of metil (CH3), triple bond (C≡C–H), group of nitril (R–C≡N), double bond (C=C) and C-N. Keyword: FTIR spectroscopy, vibration, infra red spectrum, absorption, functional group